Decolonizing reading: the Murri book club. Issue 6 (2nd November 2017) - Nolan, Maggie; Henaway, Janeese
Abstract: This article explores the cultural work of the Townsville-based Murri (Indigenous) Book Club. Although a growing body of research relates to book clubs in Britain and the US, little work has been done in the Australian context on what Marilyn Poole has called, 'one of the largest bodies of community participation in the arts in Australia' (280). The work that has been done, moreover, suggests that book clubs are an overwhelmingly white phenomenon, through which members 'maintain their currency as literate citizens through group discussion'. But what of an Indigenous book club and its concerns? This article asserts that the Murri book club challenges traditional book club expectations through its very different relationship to cultures of books and reading. In doing so, the Murri book club has taken a white, middle-class practice and reshaped it for its own purposes: decolonizing the book club as a social, cultural and political institution. By examining the origins of the book club, its approach to books and the lives of some of its members, this article also suggests that the Murri book club challenges expectations about Indigenous professionals and offers insight into the complex ways in which Indigenous professionals negotiate their identities and their relationships with other readers, through communal literary networks.